Immunotoxin-Induced Ablation of the Intrinsically Photosensitive Retinal Ganglion Cells in Rhesus Monkeys - Ostrin, Lisa A.; Strang, Christianne E.; Chang, Kevin; Jnawali, Ashutosh; Hung, Li-Fang; Arumugam, Baskar; Frishman, Laura J.; Smith, Earl L.; Gamlin, Paul D. (Frontiers in Neurology, 2018)
Purpose: The intrinsically photosensitive retinal ganglion cells (ipRGCs) contain the photopigment melanopsin, and are primarily involved in non-image forming functions, including the pupillary light reflex (PLR) and circadian rhythm entrainment. The goal of this study was to develop and validate a targeted ipRGC immunotoxin to ultimately examine the role of ipRGCs in macaque monkeys. Methods: An immunotoxin for macaque melanopsin gene (OPN4), consisting of a saporin-conjugated antibody directed at the N-terminus, was prepared in solutions of 0.316, 1, 3.16, 10, and 50 µg in vehicle, and delivered intravitreally to the right eye of six rhesus monkeys, respectively. Left eyes were injected with vehicle only. The PLR, the ipRGC-driven post illumination pupil response (PIPR) and electroretinograms (ERGs) were recorded before and after injection. For pupillography, 1 and 5 second (s) pulses of light were presented to the dilated right eye while the left pupil was imaged. Stimulation included 651 nm (133 cd/m2), and 4 intensities of 456 nm (16 to 500 cd/m2) light. Maximum pupil constriction and the 6s PIPR were calculated. Retinal imaging was performed with optical coherence tomography (OCT), and eyes underwent OPN4 immunohistochemistry to evaluate ipRGC loss. Results: Before injection, animals showed robust pupil responses to 1s and 5s blue light. After injection, baseline pupil size increased 12 ± 17%, maximum pupil constriction decreased, and the PIPR, a marker of ipRGC activity, was eliminated in all but the lowest immunotoxin concentration. For the highest concentrations, some inflammation and structural changes were observed with OCT, while eyes injected with lower concentrations appeared normal. ERG responses showed better preserved retinal function with lower concentrations. Immunohistochemistry showed 80-100% ipRGC elimination with the higher doses being more effective; however this could be partly due to inflammation that occurred at the higher concentrations. Conclusion: Findings demonstrated that the OPN4 macaque immunotoxin was targeted ipRGCs, and induced a graded reduction in the PLR and ipRGC-driven pupil response with concentration. Further investigation of the effects of ipRGC ablation on ocular and systemic circadian rhythms and the pupil in rhesus monkeys will provide a better understanding of the role of ipRGCs in primates.